High‐Energy Rechargeable Metallic Lithium Battery at −70 °C Enabled by a Cosolvent Electrolyte. (26th March 2019) - Dong, Xiaoli; Lin, Yuxiao; Li, Panlong; Ma, Yuanyuan; Huang, Jianhang; Bin, Duan; Wang, Yonggang; Qi, Yue; Xia, Yongyao
Abstract: Lithium metal is an ideal anode for high‐energy rechargeable batteries at low temperature, yet hindered by the electrochemical instability with the electrolyte. Concentrated electrolytes can improve the oxidative/reductive stability, but encounter high viscosity. Herein, a co‐solvent formulation was designed to resolve the dilemma. By adding electrochemically "inert" dichloromethane (DCM) as a diluent in concentrated ethyl acetate (EA)‐based electrolyte, the co‐solvent electrolyte demonstrated a high ionic conductivity (0.6 mS cm −1 ), low viscosity (0.35 Pa s), and wide range of potential window (0–4.85 V) at −70 °C. Spectral characterizations and simulations show these unique properties are associated with the co‐solvation structure, in which high‐concentration clusters of salt in the EA solvent were surrounded by mobile DCM diluent. Overall, this novel electrolyte enabled rechargeable metallic Li battery with high energy (178 Wh kg −1 ) and power (2877 W kg −1 ) at −70 °C.